2022
DOI: 10.1097/pas.0000000000001924
|View full text |Cite
|
Sign up to set email alerts
|

Localized Malignant Peritoneal Mesothelioma (LMPeM) in Women: A Clinicopathologic Study of 18 Cases

Abstract: Localized malignant peritoneal mesothelioma is a rare tumor with limited information in the literature. In this study, we present our experience with 18 cases seen in our hospital over a period of 43 years (1978 to 2021). Patients' median age was 55 years (y) (range: 33 to 79 y) and most of them were Caucasians. Patients presented with abdominal pain (11), ascites and right leg swelling (1), abdominal mass (1), and as incidental finding (1). Thirty percent of patients reported asbestos exposure, and all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 45 publications
(376 reference statements)
0
27
0
1
Order By: Relevance
“…Adenomatoid features are much less common in peritoneal mesothelioma 3–5 . A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors 55–61 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adenomatoid features are much less common in peritoneal mesothelioma 3–5 . A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors 55–61 .…”
Section: Discussionmentioning
confidence: 99%
“…54 Adenomatoid features are much less common in peritoneal mesothelioma. [3][4][5] A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors. [55][56][57][58][59][60][61] However, some of these cases were associated with conventional mesothelioma component, 55 and accompanying genetic analysis was not described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This figure and Figure 2 demonstrate the macroscopic and microscopic appearance of clear-cell mesothelioma that has led to the intraoperative diagnosis of clear-cell adenocarcinoma. The occurrence of extragenital clear-cell adenocarcinoma, although uncommon, could be expected, as clear-cell adenocarcinoma is common in the Eastern world, accounting for up to 27% of ovarian epithelial cancers in Japan [ 6 ], and this tumor can arise from non-ovarian endometriosis. While the diagnosis of clear-cell adenocarcinoma in the endometrium or the ovary may not require or depend on immunohistochemistry, the diagnosis of clear-cell adenocarcinoma of peritoneal origin needs to be supported by an appropriate and extensive immunohistochemical panel.…”
mentioning
confidence: 99%